2016
DOI: 10.1016/j.str.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Sugar Transporter of the Glucose EIIC Superfamily Provides Insight into the Elevator Mechanism of Membrane Transport

Abstract: Summary The phosphoenolpyruvate:carbohydrate phosphotransferase systems (PTS) are found in bacteria, where they play central roles in sugar uptake and regulation of cellular uptake processes. Little is known about how the membrane-embedded components (EIICs) selectively mediate the passage of carbohydrates across the membrane. Here we report the functional characterization and 2.55 Å resolution structure of a maltose transporter, bcMalT, belonging to the Glucose superfamily of EIIC transporters. bcMalT crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Because the crystal contacts are the same between the alternative crystal forms, the differences seen cannot be attributed to contacts. Instead, we believe the alternative crystal forms can be found in the intermediates of the MD simulation 3 . The MD simulation suggests that it is the second half of the V-motifs (TMSs 2 and 7) that are involved in capturing the substrate, and that it is the mobile nature (presumably mediated by the critical glycines) that allows capture of the substrate (cf.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Because the crystal contacts are the same between the alternative crystal forms, the differences seen cannot be attributed to contacts. Instead, we believe the alternative crystal forms can be found in the intermediates of the MD simulation 3 . The MD simulation suggests that it is the second half of the V-motifs (TMSs 2 and 7) that are involved in capturing the substrate, and that it is the mobile nature (presumably mediated by the critical glycines) that allows capture of the substrate (cf.…”
Section: Introductionmentioning
confidence: 91%
“…One of the four steps of the “Elevator Mechanism” involves a transition in which the substrate is captured (outward open to outward occluded transition). Recently, the outward occluded conformation of MalT of the GFL superfamily was solved, but the “substrate capturing step” could only be simulated using MD 3 . We have proposed that secondary structural elements can be mapped between the GFL superfamily (MalT, ChbC) and the ascorbate-galactitol (AG) superfamily (UlaA) 2 (Figure 1, Table 1 in 4 or Figure S1 and Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Transport models have been proposed involving the movement of the rigid binding site from the outward open to the inward open structure. While the structures of the N,N'-diacetylchitobiose and maltose transporters revealed a linear movement of the active site ("elevator-type mechanism") [Cao et al, 2011;Lee et al, 2017;McCoy et al, 2016], the one of the vitamin C transporter suggested a rotation ("rigidbody rotation") [Luo et al, 2015]. In each case, the inward-open structure must allow the interaction with the cognate P∼EIIB for phosphorylation of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“… In this issue of Structure , McCoy et al (2016) describe the 2.55-Å X-ray structure of the outward-facing occluded conformation of the Bacillus cereus maltose transporter MalT. This structure represents the penultimate piece needed to complete the picture of the transport cycle of the glucose superfamily of membrane-spanning EIIC components.…”
mentioning
confidence: 99%
“…The structure solved by McCoy et al (2016), described in this issue of Structure , represents the outward-facing occluded conformation of the maltose (glucosyl α-1,4-glucose) transporter MalT, which belongs to the GFL superfamily. This structure is the key to understanding the complete transport cycle from outward occluded to inward occluded and confirms the model that was proposed based on the earlier ChbC structure.…”
mentioning
confidence: 99%